Studi Perbandingan pada Pembelajaran Menulis melalui Media Video 3D Virtual Reality dan Video 2D - Moris Virgiawan; Nunuk Suryani; Leo Agung (Teknodika, 2020)
This article presents the result of the research study aimed at finding out: (1) whether there is any significant difference in writing achievement between the students taught using 3D Virtual Reality video and those taught using 2D video; and (2) whether the students taught using 3D Virtual Reality video have higher writing achievement than those taught using 2D video. The research method used in this study is quasi-experimental research design. The research instrument used to collect the data in this study is writing test. The data were analyzed by using t-test formula. The computation of the t-test shows that t-observation (to) = 2.1028 is higher than t-table (58, 0.05) = 2.0017. Therefore, it can be concluded that there is a significant difference in writing achievement between students taught using 2D video and those taught using 3D Virtual Reality video. The mean score of the experimental group improved from 67.56 to 76.55, while the mean of the score of control group improved from 67.26 to 73.25. The improvement of the experimental group is higher than the control group. It can be concluded that the students taught using 3D Virtual Reality video have higher writing achievement than those taught using 2D video.